Habitual consumption of long-chain n-3 PUFAs and fish attenuates genetically associated long-term weight gain - Huang T, Wang T, Heianza Y, Zheng Y, Sun D, Kang JH, Pasquale LR, Rimm EB, Manson JE, Hu FB, Qi L. (Am J Clin Nutr, 2019)
BACKGROUND: A growing amount of data suggests that n-3 (ω-3) polyunsaturated fatty acid (PUFA) intake may modify the genetic association with weight change. OBJECTIVES: We aimed to prospectively test interactions of habitual consumption of n-3 PUFAs or fish, the major food source, with overall genetic susceptibility on long-term weight change. DESIGN: Gene-diet interactions were examined in 11,330 women from the Nurses' Health Study (NHS), 6773 men from the Health Professionals Follow-Up Study (HPFS), and 6254 women from the Women's Health Initiative (WHI). RESULTS: In the NHS and HPFS cohorts, food-sourced long-chain n-3 PUFA intake showed directionally consistent interactions with genetic risk score on long-term changes in BMI (P-interaction = 0.01 in the HPFS, 0.15 in the NHS, and 0.01 in both cohorts combined). Such interactions were successfully replicated in the WHI, an independent cohort (P-interaction = 0.02 in the WHI and 0.01 in the combined 3 cohorts). The genetic associations with changes in BMI (in kg/m2) consistently decreased (0.15, 0.10, 0.07, and -0.14 per 10 BMI-increasing alleles) across the quartiles of long-chain n-3 PUFAs in the combined cohorts. In addition, high fish intake also attenuated the genetic associations with long-term changes in BMI in the HPFS (P-interaction = 0.01), NHS (P-interaction = 0.03), WHI (P-interaction = 0.10), and the combined cohorts (P-interaction = 0.01); and the differences in BMI changes per 10 BMI-increasing alleles were 0.16, 0.06, -0.08, and -0.18, respectively, across the categories (≤1, 1∼4, 4∼6, and ≥7 servings/wk) of total fish intake. Similar interactions on body weight were observed for fish intake (P-interaction = 0.003) and long-chain n-3 PUFA intake (P-interaction = 0.12). CONCLUSION: Our study provides replicable evidence to show that high intakes of fish and long-chain n-3 PUFAs are associated with an attenuation of the genetic association with long-term weight gain based on results from 3 prospective cohorts of Caucasians.